2010
DOI: 10.1007/s13277-010-0129-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mutations of p53 and k-ras in gastric carcinoma patients from Hunan, China

Abstract: This case-control study investigated the mutations in p53 and k-ras genes of 123 gastric carcinoma patients and 129 normal individuals from Hunan, China. By isolating genomic DNA from peripheral blood and employing polymerase chain reaction-single strand conformation polymorphism and DNA sequencing, the mutations of p53 exons-5, 6, 7, and 8 and k-ras were detected. The overall mutation frequency of p53 was 29.3%, and mutation was found in all four exons studied. The point mutations were predominant and among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Although KRAS mutations represent a prognostic factor for colorectal and lung cancer, their correlation with the biological behaviour of gastric tumours is still poorly defined [38][40].…”
Section: Discussionmentioning
confidence: 99%
“…Although KRAS mutations represent a prognostic factor for colorectal and lung cancer, their correlation with the biological behaviour of gastric tumours is still poorly defined [38][40].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the current results, Chen et al reported that p53 mutation was associated with the initiation stages of gastric cancer. 27 Although the exact mechanism remains unclear, the presence of clonal EBV in every tumor cell suggests that EBV infection precedes the final transforming event giving rise to a tumor. 28 Yet, despite the association between advanced stage and p53 overexpression in EBVaGC tissue, no prognostic significance of p53 for DFS and OS was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in Chinese population, Chen et al [55] reported TP53 mutations in GC occurring in four exons affecting codons 131, 132, 133, 135, 149, 151, 162, 167, 173, 174, and 175 of exon 5, codons 193, 197, 213, and 215 of exon 6, codons 245, 246, 248, 249, and 270 of exon 7, and codons 271, 272, 273, and 282 of exon 8. Among the mutations, G:C to A:T transitions was the highest (41.7%), followed by A:T to G:C (25%), G:C to C:G (11.1%), G:C to T:A (8.3%), A:T to T:A (2.8%), and frameshift mutation.…”
Section: Mutations Of Tp53 Gene In Esophageal and Gastric Carcinogmentioning
confidence: 99%